Integrated Service for Empowerment: The Assessment of P2TP2A in 16 Provinces - Retno Agustin; Bella Sandiata; Indriyati Suparno; Samsidar Samsidar (Jurnal Perempuan, 2019)
The increasing number of violence against women every year raises question about the effectiveness of intergrated service programs for the women victims of violence. The government established the Integrated Service Center for Women and Children Empowerment (P2TP2A) in 2002 supported by National Commission on Violence against Women (KOMNAS Perempuan) in the effort to provide protection and empowerment of women victims of violence. However, the increasingly diverse forms of violence against women have resulted in complex needs of the victims. The question arises whether the function and performance role of P2TP2A has fully answered the needs of victims or not. This article focuses on assessments conducted by KOMNAS Perempuan and Forum Pengada Layanan (FPL) in 16 provinces to re-examine the role of P2TP2A's functions and performance in meeting the needs of victims. Based on the findings of the assessment, there are still shortcomings in the system and performance of P2TP2A in providing victims’ needs, such as lack of awareness as service providers, coordination problems among institutions and limited budget. This assessment uses in-depth interviews and document studies, by including the lessons from the P2TP2A Surakarta city, Bandung district and Central Java Province.